Analysis of Distributed Generation Accommodation in Flexible Distribution Networks - Xiao, Jun; Wang, Ying; Zu, Guoqiang (Frontiers in Energy Research, 2021)
This work proposes a method to analyze distributed generation (DG) accommodation in a flexible distribution network (FDN). Firstly, the DG-load matching degree is proposed to quantitatively describe the power balance degree of DG and load in a distribution network. Secondly, the accommodation ratio of DG is proposed and divided into a DG-load accommodation ratio and DG-network-load accommodation ratio, to distinguish whether the index takes the network operational constraints into account. We derive the DG-load accommodation ratio directly from the matching degree and propose the simulation model of sequential production to solve the DG-network-load accommodation ratio. Finally, the cases of FDN under the scenarios of different matching degrees are studied and compared with those of the traditional rigid distribution network. The results show that the improvement of the accommodation ratio by upgrading the rigid distribution network to an FDN is conditional, which is related to not only the matching degree of the whole network but also that of each local network. The DG-network-load accommodation ratio will tend to the DG-load accommodation ratio if proper planning or optimization measures are taken. We find that the capacity of branches adjacent to the DG bus mainly limit the DG accommodation in the FDN, and it is recommended to relocate the DGs and enlarge the capacity of those branches.